Religious dimensions of conspiracy theories
1 online resource (xi, 294 pages)
Keywords: "Religious Dimensions of Conspiracy Theories contributes to the study of conspiracy culture by analysing the religious and esoteric dimensions of conspiracy theories. The book examines both historical and contemporary examples to explore transnational and transhistorical continuities between religious doctrines, eschatologies, and conspiracy theories. It draws on a broad range of disciplinary insights from historians, sociologists, anthropologists, and religious studies scholars. The book has a global focus and features case studies from North America, Europe, the Middle East, Asia, and Africa. This book will be of great interest to researchers of conspiracy theories, esotericism, extremism, and religion"--